Kinetics of CaCO3 decomposition at low CO2 partial pressure in a vacuum fixed bed. (5th June 2023) - Yue, Wenfei; Song, Wenli; Fan, Chuigang; Li, Songgeng
Highlights: Intrinsic reaction kinetic parameters of CaCO3 decomposition in vacuum are obtained. Criterion eliminating CO2 partial pressure on CaCO3 decomposition rate is proposed. The activation energy in vacuum is lower than that in atmospheric pressure. Abstract: Calcium looping often suffers from sintering during CaCO3 decomposition process, and CaCO3 decomposition in vacuum is a potential solution. Kinetic analysis of CaCO3 decomposition in vacuum is seldom, and most of the kinetics in the literature is obtained from thermogravimetric analyzer in atmospheric pressure. In addition, the reported kinetic data seems scattered, and varies depending on the analyzer employed. This study is focused on the intrinsic kinetics of isothermal CaCO3 decomposition in a vacuum fixed bed from 700 °C to 850 °C. Besides conventional internal/external mass transfer elimination via reducing size/increasing gas velocity, the effect of CO2 partial pressure is specially discussed under vacuum condition. It is found that, this influence could be eliminated only when the relative difference between equilibrium pressure and maximum CO2 partial pressure ( Peq -P*CO2 )/ Peq was higher than 0.98. Tests at atmospheric pressure were also conducted with the same particle size and gas volumetric feeding rate for comparison. The intrinsic reaction rate constants of CaCO3 decomposition in vacuum are 1.05 × 10 -3 s −1 – 4.76 × 10 -3 s −1 between 700 °C and 850 °C, and the activation energy of this reaction is 92.58 kJ/mol.